IGF-1 levels in Patients with Type 2 Diabetes Mellitus - Thipani Angela; Chrismis Novalinda Ginting; Linda Chiuman; Sahna Ferdinand Ginting (Majalah Kedokteran Bandung, 2021)
Type 2 Diabetes Mellitus (Type 2 DM) is a metabolic disorder group with mechanisms that include hyperglycemia, insulin resistance and hyperinsulinemia. Type 2 DM has a close association with IGF-1, where the active form of the IGF-1 becomes elevated by reason of the fact that hyperinsulinemia inhibits the production of IGF-binding proteins (IGFBP) 1/IGFBP 2. The active form of IGF-1 has the ability to promote cell proliferation and inhibit apoptosis, hence becomes one of the risk factors for cancer cell growth. This was an analytical study conducted in August at the Harapan Bunda Clinic, Medan, Indonesia to determine the difference between the IGF-1 level and blood glucose level in type 2 DM patients in different age groups. Twenty subjects with Type 2 DM participated in this study and were divided based on their age into 35-50 years old or Group 1 and 51-65 year old group or Group 2. The IGF-1 levels in both groups were compared and analyzed using the T-test dependent method. Results showed that the IGF-1 and blood glucose levels were higher in Group 1 (35-50 years old) when compared to Group 2 and the difference was significant. The change in the IGF-1 level in diabetic patients cannot be determined only by the blood sugar level.